Ethiopia Alive & Thrive Baseline Survey 2010: Households - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household survey that was conducted to gather data at baseline as a part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions, delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of IYCF practices in two regions where the IFHP operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The Ethiopia baseline survey had two broad objectives. The first objective was to gather data on the primary impact indicators of the evaluation, prior to implementation of any A&T interventions, to establish a baseline against which changes would be measured. The second objective was to assess different factors that may influence the outcomes of interest, and thus shape the impact of the primary impact indicators. These factors were determined at five different levels: 1) child, 2) maternal/caregiver, 3) household, 4) community, 5) health care providers, 6) health system. These factors will also provide useful information to interpret the results of the impact evaluation and also signal key issues to pay attention to in the process evaluation. The Ethiopia baseline survey used five separate questionnaires that aimed to capture elements along the program impact pathways. These tools include 1) a household questionnaire, 2) a staff questionnaire of HEWs, 3) a staff questionnaire of supervisors of HEWs, 4) a VCHP), and 5) a community questionnaire. The household questionnaire in Ethiopia consisted of 14 different modules covering a wide range of information both for assessing the outcomes of interests as well as factors that influence the uptake and adoption of A&T interventions, such as household food security, socioeconomic status, parental characteristics, maternal knowledge and skills about IYCF, exposure to A&T and other IYCF/nutrition interventions, exposure to media, household gender relationships, and child characteristics, e.g., age, gender, perceptions about size and birth. The questions are largely based on previously validated questions or modules.